Parental comprehension of the benefits/risks of first-line randomised clinical trials in children with solid tumours: a two-stage cross-sectional interview study - Chappuy, Hélène (BMJ Publishing Group, 2013)
OBJECTIVES: To analyse the parental understanding of informed consent information in first-line randomised clinical trials (RCTs) including children with malignant solid tumours and to assess parents’ needs for decision-making. DESIGN: Observational prospective study. SETTING: 3 paediatric oncology centres in the Parisian region in France. PARTICIPANTS: 53 parents were approached to participate in a RCT for their child with malignant solid tumour, over a 1-year period. 40 parents have been interviewed in our study. PRIMARY AND SECONDARY OUTCOME MEASURES: Parental understanding of information in RCTs, parents’ needs for decision-making. Parents were questioned by a psychologist, independent of the paediatric oncology teams, using a semidirected interview, 1 (M1) and 6 months (M6) after the consent was sought. RESULTS: 18 parents (45%) did not understand the concept of randomisation. Half of the parents could explain neither the aim of the clinical trial nor the potential benefit to their child of inclusion. 35 parents (87.5%) expressed very few specific risks related to the trial. Being mostly French-speaking (p=0.03) and the reading of the information sheet by the parents (p=0.0025) improved their understanding. The parental comprehension did not differ between M1 and M6. The principal factors underlying their decision were confidence in the medical team (39%), wish to access to the best treatment (37%) and the best quality of life (37%). CONCLUSIONS: Despite medical explanations, parents have limited knowledge in some areas in first-line RCTs and improvements of information process are required. The risks specific to the randomised trial are underestimated by parents and the unproven nature of the treatment is not well-known or understood.